Mother's Psychological Conditions in Educating Down Syndrome Children - Mahmuda, Nafila; Nozaki, Kayoko (AGENDA: Jurnal Analisis Gender dan Agama, 2024)
This study aims to describe and understand the psychological conditions of mothers in educating children with Down syndrome using qualitative methods with a case study approach. The subject in this study is a mother who has a child with Down syndrome. The results of this study indicate that educating a child with Down syndrome can affect the mother's psychological condition. At first the mother was shocked, sad and anxious after finding out her child was diagnosed with Down syndrome. Over time, the mother began to accept their child's condition and focus on how to support their child's development. However, mothers of children with Down syndrome often face higher levels of stress than mothers of children without special needs.